Certification of training and training outcomes - Acemoglu, Daron [Verfasser]; Pischke, Jörn-Steffen [Verfasser] (My University, 2000)
"External certification of workplace skills obtained through on-the-job training is widespread in many countries. This may indicate that training is financed by workers, and certification serves to assure the quality of the training offered by the firm. However, other evidence shows that general training is financed by firms, especially in Germany. We show in this paper that external certification of training may also be necessary for an equilibrium with firm-sponsored training. Firm financing of training is only possible if firms have monopsony power over the workers after training. If the training firm can extract too much of the employment rents, however, workers may not have sufficient incentives to put forth effort during training. Certification increases the value training to the outside market, and hence to workers, making firm-sponsored training possible." Die Autoren diskutieren auf modelltheoretischer Ebene die Zusammenhänge zwischen Finanzierung, Zertifizierung und Effizienz von innerbetrieblicher Aus- und Weiterbildung. (Autorenreferat, IAB-Doku)
Keywords: L 2.1.3 Erfahrungslernen; L 2.1.1 Informelles Lernen; S 4 Kosten & Finanzierung; S 2.2.4 Anrechnung, Prüfung & Zertifizierung; S 4.3.6 Human Capital; On-the-job training; Betriebliche Weiterbildung; Finanzierung; Zeugnis; Qualifikationsnachweis; Humankapitalansatz